Extract from spent hop (Humulus lupulus L.) reduces blood platelet aggregation and improves anticoagulant activity of human endothelial cells in vitro. (April 2016) - Luzak, Boguslawa; Golanski, Jacek; Przygodzki, Tomasz; Boncler, Magdalena; Sosnowska, Dorota; Oszmianski, Jan; Watala, Cezary; Rozalski, Marcin
Highlights: Spent hop extract exerts significant beneficial effects on haemostatic system. Spent hop extract has strong anti-platelet activity. Spent hop extract improves anticoagulant activity of human endothelial cells. Feeding of diabetic rats with spent hop extract significantly prolongs their lifespan. Spent hop extract can play a role in nutritional vascular protection. Abstract: Spent hop extract (SHE) is hypothesized to possess multifaceted anticoagulant effect and to reduce platelet reactivity in a direct manner and to improve the antiplatelet action of endothelium. The results demonstrated that SHE, rich in flavanols (50% of total phenolic compounds), hydroxycinnamic acids, proanthocyanidin oligomers, flavan-3-ol monomers, and flavonol glycosides, inhibited ADP-induced platelet aggregation up to 11% for 7.5 µg/ml or up to 23% for 15 µg/ml, P  <   0.05. Additionally, SHE ameliorated anticoagulant activity of human endothelial cells to significantly reduce platelet reactivity. This effect could be related to the increased expression/activity of the ecto-ADPase (CD39). ADP-induced platelet reactivity was reduced in the case of platelets incubated with the extract-treated endothelial cells compared to the untreated cells. Diabetic rats fed with SHE demonstrated longer survival time than the group treated with placebo. In conclusion, our study provided evidence for a potential beneficial role of SHE in the regulation of platelet and endothelial function.